Kajian Hukum Penerapan Ketentuan Hukuman Mati dalam Undang-Undang Tindak Pidana Korupsi - Ginting, Grenaldo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Corruption is categorized as an extraordinary crime where the impact can be very detrimental to the country and can even have a very bad impact on the economy and development of the country. Efforts to deal with and eradicate criminal acts of corruption as meant in Law Number 31 of 1999 which has been amended by Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, put forward several important points and main ideas and are considered capable of providing a deterrent effect against the perpetrators of this extraordinary crime, namely the principle of reversed proof and severe legal sanctions, including the death penalty. This research is a normative legal research. The main characteristics of normative legal science research in conducting legal studies are primary and secondary legal materials, using interpretation methods, and using normative juridical analysis. The result of this research is that the regulation on capital punishment in the PTPK Law is stated in Article 2 paragraph (2) which formulates "in the event that a criminal act of corruption as referred to in paragraph (1) is committed in certain circumstances the death penalty can be imposed". The specific situation in question is a situation that can be used as a reason for criminal aggravation for perpetrators of corruption, namely if the crime is committed against funds earmarked for overcoming a dangerous situation. Article 1 paragraph (3) of the 1945 Constitution formulates that: "Indonesia is a state based on law". The consequence of a rule of law is the protection of human rights, including the right to life. Thus, the imposition of death penalty for corruptors who have been hampered by human rights issues, especially the right to life can be upheld.